(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article discusses the role and characteristics of the international financial system in the world economy. The international financial system is a set of relations that are directly related to the movement of global funds and serve the financial and economic interstate relations and international business (foreign trade, lending, subsidies, tourism, exchange of scientific and technological developments, etc.).